2011
DOI: 10.1159/000323568
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Characterizing Trajectories of Cognitive Change in Older Persons with Mild Cognitive Impairment

Abstract: Background: Mild cognitive impairment (MCI) represents a state of high risk for dementia but is heterogeneous in its course. To date, the trajectories reflecting distinct developmental courses of cognition among patients with MCI have not been well defined. Aim: To identify the developmental trajectory of groups with distinct cognitive change patterns among a cohort of MCI patients. Methods: 187 MCI patients from 2 geriatric outpatient clinics were evaluated serially with the Mini-Mental State Examination (MMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 51 publications
7
40
1
Order By: Relevance
“…The sample for this study was identical to that examined in our previous study for which trajectories of cognitive change were identified [26]. Of 311 MCI patients, a total of 187 patients who had been administered the MMSE at their initial visit to the clinic and at least once more over a period of up to 3.5 years were included.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The sample for this study was identical to that examined in our previous study for which trajectories of cognitive change were identified [26]. Of 311 MCI patients, a total of 187 patients who had been administered the MMSE at their initial visit to the clinic and at least once more over a period of up to 3.5 years were included.…”
Section: Methodsmentioning
confidence: 99%
“…Of 311 MCI patients, a total of 187 patients who had been administered the MMSE at their initial visit to the clinic and at least once more over a period of up to 3.5 years were included. This subgroup did not differ by age, sex, education, language, or baseline MMSE score from the 124 who were not administered the MMSE at their initial visit or who had the MMSE only once [26]. The average number of MMSE administrations for included patients was 4 (±1.7; range 2–9).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Xie and colleagues [16] used groupbased trajectory analysis to identify distinct cognitive change patterns among a cohort of 187 MCI patients from two geriatric outpatient clinics over a course of up to 3.5 years. Five trajectories were identified and labeled based on their baseline MMSE score.…”
Section: Discussionmentioning
confidence: 99%